Pemanfaatan Gel Ekstrak Kulit Buah Mangga Arumanis (Mangifera indica L.) Sebagai Antiinflamasi Dengan Metode Kantong Granuloma Secara In-Vivo - Ifmaily Ifmaily; Hastri Delfa Yenti; Meta Emillia Surya Dharma (Pusat Riset dan Inovasi Nasional, 2023)
In previous research, mango rind extract has been studied as an antioxidant, antihypertensive, and antidiabetic, because it contains flavonoids and 17% mangiferin compounds. In this research, the effect of arumanis mango rind extract gel (Mangifera indica L.) as an anti-inflammatory was tested in male white mice induced by carrageenan using the granuloma pouch method. This experimental study used experimental white male mice which were grouped into 5 groups: the control group, the group with 2% mango rinf extract, the group with 4% mango rind extract, the group with 8% mango rind extract, and the comparison group. The parameters that were analyzed were exudate volume, total leukocytes, and type of leukocytes on days 3, 5, 7. The results showed that mango arumanis (Mangifera indica L.) rind extract had anti-inflammatory effectiveness topically as indicated by a decrease in the average exudate volume, total leukocytes, and leukocyte cell types (segmented neutrophil cells and lymphocyte cells) in each concentration group of mango rind extract, based on two-way ANOVA test and Duncan's test showed significant differences with respect to concentration and time (p<0.05). It can be concluded that all gel concentrations of arumanis mango rind extract (Mangifera indica L.) 2%, 4%, and 8% have anti-inflammatory effects.